2009
DOI: 10.1002/9780470584330.ch20
|View full text |Cite
|
Sign up to set email alerts
|

Pressureless Reaction Sintering of AlON Using Aluminum Orthophosphate as a Transient Liquid Phase

Abstract: Use of aluminum oxynitride (AlON) in transparent armor systems has been difficult due to the expense and limitations of the processing methods currently necessary to achieve transparency. Development of a pressureless processing method based on direct reaction sintering of alumina and aluminum nitride powders would reduce costs and provide a more flexible and practical manufacturing method. It may be possible to develop such a processing method using liquid phase sintering; as long as the liquid phase does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…6 Several reviews have already been published, giving a thorough description of the extensive effort dedicated to this class of materials. [7][8][9][10] Magnesium aluminate (MgAl 2 O 4 ) spinel -simply called spinel from now on -has a cubic crystal structure and is therefore optically isotropic. In addition to a high melting point, it has excellent mechanical properties, outstanding hardness and a superb transparency from the near UV down to the mid IR * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several reviews have already been published, giving a thorough description of the extensive effort dedicated to this class of materials. [7][8][9][10] Magnesium aluminate (MgAl 2 O 4 ) spinel -simply called spinel from now on -has a cubic crystal structure and is therefore optically isotropic. In addition to a high melting point, it has excellent mechanical properties, outstanding hardness and a superb transparency from the near UV down to the mid IR * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has discovered that certain additives can be beneficial to the sintering of AlON. Hartnett, Gentilemen, and Macquire have reported that additives such as yttrium and lanthanum improve the sintering and microstructure of AlON, and subsequent researchers have also reported on the beneficial nature of these additives [14]. Not only must the correct additive be identified, but numerous processing variables such as compositions, maximum temperature, and holding times must be defined if porosity or swelling is to be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent spinel‐type polycrystalline ceramics like MgAl 2 O 4 and γ‐AlON have been widely studied. They possess both optical transparency from ultraviolet to middle‐infrared wavelengths and excellent mechanical properties, which makes them as promising candidates instead of sapphire for transparent armors, missile domes, window materials, etc.…”
Section: Introductionmentioning
confidence: 99%